2020
DOI: 10.5194/gmd-13-6265-2020
|View full text |Cite
|
Sign up to set email alerts
|

A fast and efficient MATLAB-based MPM solver: fMPMM-solver v1.1

Abstract: Abstract. We present an efficient MATLAB-based implementation of the material point method (MPM) and its most recent variants. MPM has gained popularity over the last decade, especially for problems in solid mechanics in which large deformations are involved, such as cantilever beam problems, granular collapses and even large-scale snow avalanches. Although its numerical accuracy is lower than that of the widely accepted finite element method (FEM), MPM has proven useful for overcoming some of the limitations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
(115 reference statements)
0
3
0
Order By: Relevance
“…The GPU-based algorithm relies heavily on the use of arrays p2e and e2n (Wyser et al, 2020a). Elements are numbered with an increasing index.…”
Section: Back-and-forth Mapping Between Materials Points and Their Associated Nodesmentioning
confidence: 99%
See 2 more Smart Citations
“…The GPU-based algorithm relies heavily on the use of arrays p2e and e2n (Wyser et al, 2020a). Elements are numbered with an increasing index.…”
Section: Back-and-forth Mapping Between Materials Points and Their Associated Nodesmentioning
confidence: 99%
“…The wall-clock time for Model 1b is t GPU = 1470.5 s (25 min), and the number of iterations per second is 85.5 iterations s −1 for n mp = 819 200. As a preliminary example, the same numerical model was performed by Wyser et al (2020a), who reported 19.98 iterations s −1 for n mp = 12 800. Proportionally, this corresponds to a performance gain factor of 275 for the GPU-based implementa- tion (ep2-3De v1.0) over the MATLAB-based implementation (fMPMM-solver v1.1) (Wyser et al, 2020a).…”
Section: Collapse Limitationmentioning
confidence: 99%
See 1 more Smart Citation